Mediation of Divorce Disputes by the Village Government: The Perspective of Progressive Legal Theory and Maqasid Syariah Jasser Auda - Mawardi Mawardi; Roibin Roibin; Musleh Harry; Zaenul Mahmudi; Musataklima Musataklima (Syura: Journal of Law, 2026)
The increasing rate of divorce in Indonesia indicates that marital conflicts are no longer merely private matters but have evolved into broader social issues affecting community stability. In addition to litigation through religious courts, community-based alternative dispute resolution mechanisms emphasizing deliberation and local wisdom have developed, one of which is mediation conducted by village governments. This study aims to analyze the effectiveness of divorce dispute mediation carried out by the Village Government of Banra’as, Sumenep Regency, and to examine the practice from the perspectives of progressive legal theory and maqasid al-sharia as proposed by Jasser Auda. This research employs an empirical legal method with a qualitative approach. Data were collected through field observations, interviews with village officials and relevant stakeholders, as well as documentation studies, and were analyzed using descriptive-analytical techniques. The findings reveal that village mediation plays a significant role in reducing domestic conflicts and encouraging reconciliation between spouses before cases are brought to the religious court. From the perspective of progressive law, this practice reflects a humanistic, flexible, and substantively just legal approach. Meanwhile, from the perspective of maqasid al-sharia, village mediation represents an effort to preserve family welfare (hifz al-nasl), maintain social stability, and promote holistic societal well-being. Therefore, mediation conducted by village governments can be regarded as an effective and contextual dispute resolution model that aligns with both legal values and socio-religious norms.